Comparison of Mineral Trioxide Aggregate and Calcium Hydroxide as pulpotomy agents in Primary Molars - Uddin, Md Farid; Alam, Md Shamsul; Moral, Ali Asgor; Howlader, Md Mujibur Rahman; Hossain, Md Ismail (Update Dental College Journal, 2014)
Background: The greatest threats to developing teeth are dental caries and traumatic injury. If pulpal exposure occurs, then a pulpotomy procedure aims to preserve pulp vitality to allow for normal root development. Historically, calcium hydroxide has been the material of choice for pulpotomy procedures. Recently, an alternative material called mineral trioxide aggregate (MTA) has demonstrated the ability to induce hard-tissue formation in pulpal tissue. Objectives: This prospective study was conducted to observe the clinical and radiological findings of pulpotomies done with Mineral Trioxide Aggregate (MTA) &Calcium Hydroxide{Ca(OH)2} and to evaluate success rate of MTA in maintaining pulpal health in teeth with carious lesion. Materials and Methods: In this clinical trial study, 40 primary molars were treated by a conventional pulpotomy technique. They all fulfill the inclusion criteria and gave consent regarding this study. All selected teeth were evenly divided into 2 test groups. In group 1, the MTA pulpotomy (experimental) was performed, whereas in group 2, the conventional Ca(OH)2 pulpotomy (control) was done. The teeth of both groups were finally restored by Glass Ionomer Cement (GIC). The children were recalled for clinical and radiographic evaluations after 3, 6, and 12 months. Result: The follow-up evaluations revealed failure due to pain and swelling detected at 6 and 12 months postoperative evaluations in only 3 teeth treated with Ca(OH)2 and one treated with MTA. The remaining 36 teeth appeared to be clinically and radiographically successful 12 months postoperatively. Calcific metamorphosis was a radiographic finding in 4 teeth treated with MTA and 2 teeth treated with Ca(OH)2. Conclusion: Based on this clinical and radiographical evaluation study of 3, 6, and 12 months follow-up, MTA could be used as a safe material for pulpotomy in cariously and mechanically exposed primary molars and seems to be a suitable alternative to calcium hydroxide. Further research, however, is required to clarify this conclusion. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17981 Update Dent. Coll. j: 2013; 3 (1): 24-31